Aberrant long-range functional connectivity density in generalized tonic-clonic seizures. Issue 24 (June 2016) - Zhu, Ling; Li, Yibo; Wang, Yifeng; Li, Rong; Zhang, Zhiqiang; Lu, Guangming; Chen, Huafu
Abstract : Abstract: Studies in generalized tonic-clonic seizures (GTCS) have reported both structural and functional alterations in the brain. However, changes in spontaneous neuronal functional organization in GTCS remain largely unknown. In this study, 70 patients with idiopathic generalized epilepsy characterized by tonic–clonic seizures and 70 age- and sex-matched healthy controls were recruited. Here, functional connectivity density (FCD) mapping, an ultrafast data-driven method based on functional magnetic resonance imaging (fMRI), was applied for the first time to investigate the changes of spontaneous functional brain activity caused by epilepsy. The results showed significantly decreased long-range FCD in the middle and inferior temporal, prefrontal, and inferior parietal cortices as well as increased long-range FCD in the cerebellum anterior lobe and sensorimotor areas. Negative correlation between duration of disease and reduced long-range FCD was found. In addition, most regions with reduced long-range FCD showed decreased resting-state functional connectivity (rsFC) within default mode network. Negative correlation between duration of disease and long-range FCD may reflect an adverse consequence eventually from original. Furthermore, the observed FCD and rsFC alterations have been speculated to be associated with the social–cognitive impairments as well as motor control. Our study provided novel evidences to look into neuro-pathophysiological mechanisms underlying GTCS. Abstract : Supplemental Digital Content is available in the text